2022
DOI: 10.9734/ajess/2022/v37i2796
|View full text |Cite
|
Sign up to set email alerts
|

Embracing the Unknown: Adaptability and Resiliency of Out-of-Field Secondary Teachers Teaching English in Public Schools

Abstract: Out-of-Field Teaching (OFT) has become one of the common concerns of different educational institutions in the global arena. Its prevalence worldwide has become a major issue because of its impact on the quality of education and the efficacy of teachers. Due to the shortage of specialized teachers in the field, school heads opted to hire out-of-field teachers to teach English subjects which creates a detrimental effect on professional growth, teachers’ performance, and the well-being of teachers. Thus, this qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…As Albahiri and Alhaj [20] have said, research has shown that when teachers are engaged in professional development, such as graduate education, it can develop their skills and knowledge. As Roberto and Madrigal [21] and Buenacosa and Petalla [22] supported, graduate education can improve expertise, competencies, and teaching mindsets, advancing professional development and effectively applying 21 st -century teaching skills. The findings imply that these teachers practiced 21 st -century teaching skills.…”
Section: Extent Practice Of 21 St Century Teaching Skills Of Teachersmentioning
confidence: 99%
“…As Albahiri and Alhaj [20] have said, research has shown that when teachers are engaged in professional development, such as graduate education, it can develop their skills and knowledge. As Roberto and Madrigal [21] and Buenacosa and Petalla [22] supported, graduate education can improve expertise, competencies, and teaching mindsets, advancing professional development and effectively applying 21 st -century teaching skills. The findings imply that these teachers practiced 21 st -century teaching skills.…”
Section: Extent Practice Of 21 St Century Teaching Skills Of Teachersmentioning
confidence: 99%
“…;Petalla & Madrigal, 2017;Malagsic et al, 2021;Buenacosa & Petalla, 2022). More so, teachers could affect learning in larger contexts more effectively by inspiring students.…”
mentioning
confidence: 99%